Biologic Sequencing in Systemic Lupus Erythematosus: After Secondary Non-response to Rituximab, Switching to Humanised Anti-CD20 Agent Is More Effective Than Belimumab - Hassan, Sabih Ul; Md Yusof, Md Yuzaiful; Emery, Paul; Dass, Shouvik; Vital, Edward M. (Frontiers in Medicine, 2020)
Background: Rituximab is commonly used for systemic lupus erythematosus (SLE) but secondary non-depletion and non-response (2NDNR) associated with anti-drug antibodies is a notable problem with repeat rituximab cycles. Other B cell-targeted therapies include other anti-CD20 monoclonal antibodies or belimumab. Objective: To compare efficacy of switching to alternative anti-CD20 agents versus belimumab in SLE patients with 2NDNR to rituximab. Methods: 125 patients received rituximab and had evaluable data. 77/125 received repeat rituximab cycles. Of these, 14/77 (18%) had 2NDNR. 8/14 patients were switched to belimumab (CD20-to-belimumab group) and 6/14 patients were switched to an alternative humanised anti-CD20 agent (CD20-to-CD20 group, ocrelizumab n=3, ofatumumab n=2, obinutuzumab n=1). Efficacy was assessed using the BILAG-2004, SLEDAI-2K, SRI-4, and daily prednisolone requirement at baseline and 6 months. Results: In the CD20-to-belimumab group, only one patient achieved an SRI-4 and 2/8 patients had new/worsening BILAG-2004 grade A for lupus nephritis. There was no improvement in SLEDAI-2K; median (IQR) was 11.0(9.5-14.8) at baseline and 10(9.5-15.5) at 6 months. Median (IQR) prednisolone dose increased from 7.5mg (4.4-12.5) to 10mg (6.3-10). In the CD20-to-CD20 group, all 6 patients achieved an SRI-4. Median (IQR) SLEDAI-2K improved from 16.0(10.3-24.0) at baseline to 5.0(2.5-6.0) at 6 months. Median (IQR) prednisolone dose decreased from 15mg (15-15) to 10.5mg (5.3-15.0). Conclusion: This is the first assessment of belimumab’s efficacy in a post-rituximab population. Our data suggests that patients with 2NDNR to rituximab, which constituted 11% of all patients initiated on this drug, should be switched within the same biologic class to another anti-CD20 agent.